IMPLEMENTASI NILAI LINGKUNGAN PADA KERANGKA EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) MELALUI PEMBELAJARAN IPAS DI SDN KARANGSEMANDING 02 - Nisa', Zahrotun; Nafi'ah, Jamilatun (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to comprehensively describe the planning, implementation process, and evaluation of learning that integrates environmental values within the framework of Education for Sustainable Development (ESD) in the IPAS subject. The focus of this research is the integration of sustainability values, with the participants consisting of two fourth-grade teachers and fourth-grade students at SDN Karangsemanding 02. This study employed a qualitative approach using a case study design. Data were collected through participant observation, semi-structured interviews, and document analysis of teaching modules. The data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that the implementation of environmental values within the ESD framework was implicitly integrated through the adaptation of teaching modules to local conditions and contextual project-based activities, such as waste sorting and recycling. The study identified three prominent environmental pillars of ESD: environmentally responsible behavior, ecological awareness, and environmental conservation, with the highest indicators observed during the implementation and evaluation stages. The simplified deep learning approach applied in this study proved effective in gradually facilitating the internalization of values, in line with Vygotsky’s theory. In conclusion, the integration of environmental values through the ESD framework contributes to the development of students’ sustainability-oriented character through contextual learning that is relevant to the school’s environmental conditions.